SUBSTITUSI TEPUNG KACANG KEDELAI (Glycine max L.) DAN PISANG RAJA (Musa paradisiaca L. var sapientum) TERHADAP MUTU KIMIA, MUTU GIZI, DAN MUTU ORGANOLEPTIK SNACK BAR BAGI PENDERITA HIPERTENSI: Substitution of Soybean Flour (Glycine Max L.) and Plantain (Musa Paradisiaca L. Var Sapientum) on Chemical Quality, Nutritional Quality, and Organoleptic Quality of Snack Bars for Hypertension Sufferers - Razak, Maryam; Suwita, I Komang; Damayanti, Yuan Dika (Media Gizi Pangan, 2024)
World Health Organization (WHO) 2018 shows that around 26.4% of the world's population has hypertension by comparison to 26.6% of men and 26.1% of women. According to Riskesdas (2018), hypertension sufferers in Indonesia reached 8.4% at the age of ≥ 18. One of the ways to prevent this case to develop a snack bars formula made with local ingredients. The processing of this snack bar is expected to become a high-potassium snack. The purpose of this study was to analyze the effect of soybean and plantain flour substitution on chemical quality (moisture content, ash content), nutritional quality (protein, fat, carbohydrates, energy, potassium), and organoleptic quality (color, aroma, taste, texture) snack bar for hypertension sufferers. This study used a completely randomized design (CRD) with three treatment levels and 12 experimental units, with the proportions of wheat flour: soybean flour: plantain, P0 (100:0:0), P1 (30: 40: 30), P2 (30: 50: 20), and P3 (30: 60:10). The results showed that the substitution of wheat flour, soybean flour, and plantains in the snack bar had a significant effect on the water content. However, it was not significant for ash content, protein, fat carbohydrates, energy value potassium content, color, aroma, taste, and texture. The best treatment of snackbar at P3 (30: 60: 10).